Filsafat Ilmu: Ontologis, Epsitemologis Dan Aksiologis Dan Kesesuainnya Masing-Masing - Amrudin . (CV. ITTC INDONESIA, 2025)
The development of science in this modern era shows a tendency towards the separation of disciplines from their philosophical roots, which reaffirms the urgency of the philosophy of science as a foundation for understanding the nature, process, and purpose of science. This research aims to examine the three main pillars of science: ontology, epistemology and axiology.The method used is library research, analyzing classical and contemporary philosophical literature. The data is processed using content analysis, descriptive, comparative, and interpretative techniques.The results of the study show that Ontology discusses schools of thought such as monism, dualism, and nihilism. Epistemology covers rationalism, empiricism, and positivism, while Axiology examines objectivism, subjectivism, and value ethics. The conclusion indicates that the integration of ontology, epistemology, and axiology is an absolute requirement to ensure that science is not only methodologically correct, but also beneficial and ethically responsible in life.